Developing distributed and e-commerce applications - Ince, Darrel (Pearson / Prentice Hall, 2003)
The last three years have seen an incredible growth of interest in distributed systems which address the business needs of companies, and which use network technology - primarily the technology employed in the internet. This book is about the development of e-commerce and e-business systems using the new technologies that have emerged or have matured over the last few years, such as web servers, CORBA, HTML, XML and Java. It looks in particular at more challenging applications where major problems in performance and reliability need to be addressed. Using a bottom-up approach, the book discusses client/servers and distributed development paradigms, before moving on to more specific technologies that are examples of the above concepts. The final part of the book covers advanced topics, such as internet security, concurrency, agents, and ubiquitous/mobile computing.